Industry 4.0 and open innovation in startups accelerators - Ottonicar, Selma Leticia Capinzaiki [UNESP] (2021)
Introduction: startups are organizations that emerge in a context of information and communication technologies. At the beginning of their foundation, startups can count on accelerators that subsidize them, through advice on how to develop the business plan, connect startups with partners and seek financial investments so that they can develop. From this perspective, startup accelerators develop open innovation processes with various stakeholders, aiming to share information and knowledge. Some startups have started to offer artificial intelligence and internet of things products and services. Such connected products are part of what is called the ’Fourth Industrial Revolution’, also known as Industry 4.0. In this scenario, this research aims to debate aspects on the themes of open innovation, accelerators, startups and Industry 4.0, demonstrating that they are interrelated and fundamental elements for the competitiveness of startups. Method: the work uses bibliographic research as a methods. Results: the results and discussions show that startups work in a collaborative environment because they need to share knowledge to develop the business plan, make decisions, seek investments, solve problems and face market challenges, since they are high-end organizations risk. Conclusion: the relationship with local politics, business associations, research institutes, universities, investors and partners contributes to building knowledge and obtaining a competitive advantage for startups that are part of the Industry 4.0 context.